Sealing Compositions Based on Polysulfide Oligomers Obtained by a Modified Method - Z.K. Myshyrova; M.I. Tulepov; L.R. Sassykova; R. Busquets (Eurasian Chemico-Technological Journal)
The article is devoted to the study of the physical and mechanical properties of composites based on polysulfide oligomers (PSO) filled with carbon black (CB) grade K-354 and multi-walled carbon nanotubes (MWCNTs). The purpose of this work was to study composites obtained by a modified method of thiocol synthesis using sodium sulfide and sodium hydrosulfate. It was revealed that the introduction of nanotubes to the thiocol matrix into the composition leads to a significant change in elastic-strength properties, leading to an increase in tensile strength by 16%. At the same time, the elongation at break decreases by 15%. Thus, in this work, the possibility of obtaining thiocols in a new way with satisfactory physical and mechanical properties was demonstrated. The work also assessed the resistance of composites to the action of aggressive substances after exposure of composites in various media (gasoline, benzene, concentrated acids), it was noted that the introduction of MWCNT increases this indicator.